7 Dispatch of fire-fighters and police officers in out-of-hospital cardiac arrest: a nationwide prospective cohort trial. (21st May 2017) - Hasselqvist-Axe, I; Nordberg, P; Herlitz, J; Svensson, L; Jonsson, M; Lindqvist, J; Ringh, M; Claesson, A; Björklund, J; Andersson, JO; Ericson, C; Lindblad, P; et al.
Abstract : Aim: Dual dispatch of cardiopulmonary resuscitation (CPR) -trained fire-fighters or police officers equipped with automated external defibrillators (AEDs) in addition to emergency medical services (EMS) in out-of-hospital cardiac arrest (OHCA) has in some minor cohort studies been associated with improved survival. The aim of this study was to evaluate the association between dual dispatch and survival in OHCA at a national level. Methods: This prospective, cohort study was conducted January 1st, 2012, to December 31st, 2014. OHCA victims in nine Swedish counties covered by dual dispatch and resuscitation by first responders and EMSs were compared with a propensity-matched contemporary control group of OHCA victims in 12 counties where only EMS were dispatched. The primary outcome was survival to 30 days. Results: 8698 OHCA were included of which 2786 in each group (intervention and control) were matched. The median time from emergency call to arrival of EMSs or first responder was nine minutes in the intervention group vs. ten minutes in the controls (p<0.001). The proportion of patients admitted alive to hospital was 31.4% in the intervention group versus 24.9% in the controls (adjusted OR 1.40, 95% CI 1.24–1.57). Thirty-day survival was 9.5% in the intervention group versus 7.7% in the controls (adjusted OR 1.27, 95% CI 1.05–1.54). Conclusion: Dual dispatch of first responders in addition to EMSs in OHCA was associated with a moderate but significant increase in 30 day survival. References: Myerburg RJ, Fenster J, Velez M, Rosenberg D, Lai S, Kurlansky P, Newton S, Knox M and Castellanos A. Impact of community-wide police car deployment of automated external defibrillators on survival from out-of-hospital cardiac arrest. Circulation. 2002;106:1058–64. PMID: 12196329 Hollenberg J, Riva G, Bohm K, Nordberg P, Larsen R, Herlitz J, Pettersson H, Rosenqvist M and Svensson L. Dual dispatch early defibrillation in out-of-hospital cardiac arrest: the SALSA-pilot dagger. European Heart Journal. 2009;30:1781–1789. doi:10.1093/eurheartj/ehp177. Malta Hansen C, Kragholm K, Pearson DA, Tyson C, Monk L, Myers B, Nelson D, Dupre ME, Fosbol EL, Jollis JG, Strauss B, Anderson ML, McNally B and Granger CB. Association of Bystander and First-Responder Intervention With Survival After Out-of-Hospital Cardiac Arrest in North Carolina, 2010–2013. JAMA: the journal of the American Medical Association. 2015;314:255–64. doi: 10.1001/jama.2015.7938. Conflict of interest: None declared. Funding: The Swedish Heart–Lung Foundation, the National Board of Health and Welfare, and the Laerdal Foundation for Acute Medicine in Norway.